(3fRgI Phi GdCdHGH hJMaI fLHGA GdCfLGHs - (3eMeO Hf CMeO Hf eMeO HfjSjs
(3ChdgG (B:s
(3GdMeO ddg hHYO ajbhd GdYHO GdabjQ Edi ehdGg eMeO Hf CMeO Hf eMeO HfjS gPg ahGFO EfJNHJgG hfcJ EfJbjJgG dJchf MdjI dTQM GdefjI dfGXegG SjOi GdEeGe MLI GdESdGe CHj YHO Gddg SjOi eMeO Hf ZGRi s
(3BNQgG (B:s
(3hcGf GdaQGZ ef gPg GdMGTjI eY bQGAI GdfXe hSQO GdTQM jhe GdehdO GdfHhi Ydi UGMHI CaVd GdUdGI hCRci GdSdGe ai YGe (B1200 (3hgPG GdYOO HOhf UaQ eQHY QHYg jSGhi KdGKI CQHGYg heQHY fUag jSGhi KdGKI CeKGdg agh KdK eQHY fUag agh eLehY MQha bhd dSGf Gs
(3GdfSNI HgG MhGTs
(3HgG HYV LOGhd GdMSGH HGdMHQ GdCMeQ GdfSNI eQbeIs
(3fSNI YdjgG eWGdYI s
(3hYdi ghGeTgG JUMjMGJ hTQhM s
(3hgj eYfhfg HGdMHQ GdCShO s
(3bQf GdfSN (B:s
Keywords: (3GdQjGVjGJs